Metaphors Design for Museum of Arab Civilization in Golden Age of Islam (The Astrolabe), UAE - Alkhalifeh, Sally (Jurnal Mahasiswa Departemen Arsitektur, 2025)
ABSTRACT   The Museum of Arab Civilization in the Golden Age of Islam (The Astrolabe) meticulously integrates metaphorical and functional elements, addressing security, visitor engagement, preservation, and sustainability. Its design incorporates Islamic astronomical metaphors, Qibla direction, and prayer times, celebrating the intellectual heritage of Muslim scholars. Adorned with Islamic geometric motifs and Arabic calligraphy, the museum's spaces provide immersive environments for cultural enrichment and historical education. A steel structure ensures durability and expansive, column-free interiors, while symbolic materials like Calacatta tiles, Ablaq stone, and Umayyad-style columns enhance authenticity. Advanced security measures, including 24/7 surveillance and IoT technology, safeguard artifacts and ensure visitor safety. The museum aims to inspire curiosity and education, offering a journey through time that introduces contemporary university researchers to the rich historical foundation on which their university was built. It demonstrates how Islamic contributions shaped the world today and laid the foundation for modern civilization, confronting historical marginalization. Future enhancements may include AR and VR for interactive experiences and collaborations with academic institutions to enrich educational programs. By celebrating the profound impact of Islamic heritage on global civilization, the museum preserves the past and empowers future generations to embrace and build upon this illustrious history.   Keywords: Integration, Metaphors Design, Islamic Geometry, Islamic Architecture